Practical system approaches to realise the human rights to water and sanitation: results and lessons from Uganda and Cambodia. Issue 1 (21st February 2022) - Kimbugwe, C.; Sou, S.; Crichton-Smith, H.; Goff, F.
Abstract: The United Nations General Assembly's 2010 legal recognition of the human rights to water and sanitation shaped approaches of many actors working to improve access to water, sanitation and hygiene (WASH). Persistent challenges of poor WASH sustainability, scale and inclusion are increasingly being tackled through system thinking and system strengthening. However, little has been written about how participatory system analysis and monitoring can equip and empower WASH actors to apply system thinking, self-assess and course-correct in their own work to improve sustainable WASH for all. WaterAid's Sustainable WASH Services at Scale (SusWASH) programme applies a system approach, underpinned by human rights principles. In this paper, we share perceptions of local stakeholders, engaged in empowerment evaluation in Cambodia and Uganda, and lessons learned for future initiatives that seek to catalyse WASH system improvements for the realisation of the human rights to water and sanitation. We argue that a system approach, underpinned by human rights principles, can help advance progress towards inclusive and sustainable WASH for all. Working in this way fosters inclusive, locally led decision-making about how system blockages can be overcome, strengthening local ownership of a shared vision for change and the capacities and skills required to achieve it. HIGHLIGHTS: WaterAid's approach seeks to tackle systemic blockages to WASH sustainability, inclusion and scale. This paper illustrates how empowerment evaluation, system concepts and human rights principles can coalesce into a practical, accessible, participatory approach that helps to strengthen WASH systems.